Adjunctive treatment with high-titre convalescent plasma in severely and critically ill COVID-19 patients – a safe but futile intervention. A comparative cohort study. Issue 11 (2nd November 2021) - Hoepler, Wolfgang Paul; Weidner, Lisa; Traugott, Marianna Theresia; Neuhold, Stephanie; Meyer, Elias Laurin; Zoufaly, Alexander; Seitz, Tamara; Kitzberger, Reinhard; Baumgartner, Sebastian; Pawelka, Erich; Karolyi, Mario; Grieb, Alexander; et al.
Abstract: Background: Convalescent plasma (CP) containing antibodies derived from coronavirus disease 2019 (COVID-19) survivors has been proposed as a promising therapeutic option for severe COVID-19. Methods: In our intensive care unit (ICU), 55 patients (46 male, median age 61 years) with PCR-confirmed COVID-19 (35 = 63.6% on mechanical ventilation, 7 = 14.5% on high-flow nasal oxygen, 12 = 20% on non-invasive ventilation, 1 = 1.8% without respiratory support) were treated with high-titre CP (200 mL per dose, range 1–6 doses, median 3 doses per patient, minimum titre > 1:100, Wantai test). 139 COVID-19 patients treated in the same ICU who did not receive CP served as control group. In 27 patients, the effect of CP on the individual levels of SARS-CoV-2 IgG antibodies was assessed by ELISA in serum sample pairs collected before and after CP transfusion. Results: The first CP dose was administered at a median of 8 days after symptom onset. 13 patients in the plasma cohort died (28-day mortality 24.1%), compared to 42 (30.2%) in the cohort who did not receive CP ( p = 0.5, Pearson Chi-squared test). Out of the 27 individuals investigated for the presence of IgG antibodies, 8 did not have detectable IgG levels before the first CP transfusion. In this subpopulation, 3 patients (37.5%) died. Not a single confirmed adverse reaction to CP was noted. Conclusions: While adjunctive treatment with CP for severe and life-threatening COVID-19 was a very safe intervention, we did not observe any effect on mortality.